2018
DOI: 10.1021/acs.iecr.8b00529
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Thermal Cross-Linking and Decomposition of Side Groups to Mitigate Physical Aging in Poly(oxyindole biphenylylene) Gas Separation Membranes

Abstract: Physical aging in amorphous polymers causes a decrease in specific volume and thus in the gas transport properties of their membranes. In this work, the effect of simultaneous thermal decomposition of a thermolabile tert-butyl carbonate group, BOC, and cross-linking by a propargyl group (−CH2–CCH) on the gas selectivity–permeability properties of the resulting membranes is studied to learn how membranes with mitigated variations in the gas permeability coefficients with aging time may be produced. The model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Thermal cross-linking of acetylene-terminated oligoimides for fabrication of composite structures using vacuum-assisted resin transfer molding (VARTM) was also described by Connell and co-workers . Controlled thermal cross-linking of poly­(oxyindole biphenylylene) membranes bearing functional propargyl groups has also been reported recently . We have found that the PI D1-ODPA-B containing propargyl groups becomes insoluble after heating at 250 °C for 1 h in vacuum, thus implicating that the trimerization reactions among three acetylene end groups take place (Scheme ) without the evolution of any volatile compounds.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Thermal cross-linking of acetylene-terminated oligoimides for fabrication of composite structures using vacuum-assisted resin transfer molding (VARTM) was also described by Connell and co-workers . Controlled thermal cross-linking of poly­(oxyindole biphenylylene) membranes bearing functional propargyl groups has also been reported recently . We have found that the PI D1-ODPA-B containing propargyl groups becomes insoluble after heating at 250 °C for 1 h in vacuum, thus implicating that the trimerization reactions among three acetylene end groups take place (Scheme ) without the evolution of any volatile compounds.…”
Section: Resultsmentioning
confidence: 54%
“…50 Controlled thermal cross-linking of poly(oxyindole biphenylylene) membranes bearing functional propargyl groups has also been reported recently. 51 We have found that the PI D1-ODPA-B containing propargyl groups becomes insoluble after heating at 250 °C for 1 h in vacuum, thus implicating that the trimerization reactions among three acetylene end groups take place (Scheme 5) without the evolution of any volatile compounds.…”
Section: Resultsmentioning
confidence: 91%
“…In cases where lower degrees of functionalization were achieved, the observed signal around 9 ppm, corresponds to the amide proton associated with the isatin, corroborating the partial modication. 24 The organogel polyelectrolytes were obtained by dissolving the cationic bbers 10% w/ v in DMSO, the high molecular weight and phase segregation allow a three-dimensional arrangement tentatively due to the strong ionic interactions of the graed fragment and the high hydrophobicity in the polymer backbone, leading to gelation processes without the need of chemical cross-linkers.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Indeed, asymmetric polymeric porous membranes with excellent thermal ( T D > 500 °C) and solvent resistance for ultrafiltration in organic solvents were prepared via cross-linking of polymer 2aA (poly­[(2-oxo-2,3-dihydro-1 H -indol-3-ylidene)­([1,1′-biphenyl]-4,4′-diyl)] using reactions with dibromoalkanes and functionalization with alkyne side groups, followed by wet-state cyclotrimerization in hot glycerol . More recently, polymer 2aA was used as a model for incorporating thermolabile and cross-linkable groups to illustrate how different thermal treatments lead to POXINAR membranes that not only possess attractive gas permeability and selectivity properties but also are more resistant to aggressive solvents and aging . An unusual and very interesting example of thermal cross-linking of a 2aA membrane followed by long-term annealing under vacuum (10 –3 Torr) was reported; the resulting polymers were resistant to solvent swelling and CO 2 plasticization up to 18 bar, and the selectivity–permeability combinations for O 2 /N 2 overcome the typical trade-off between permeability and selectivity, falling above Robeson’s 2008 upper-bound limit.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recently, polymer 2aA was used as a model for incorporating thermolabile and cross-linkable groups to illustrate how different thermal treatments lead to POXINAR membranes that not only possess attractive gas permeability and selectivity properties but also are more resistant to aggressive solvents and aging. 9 An unusual and very interesting example of thermal cross-linking of a 2aA membrane followed by long-term annealing under vacuum (10 −3 Torr) was reported; 10 the resulting polymers were resistant to solvent swelling and CO 2 plasticization up to 18 bar, and the selectivity−permeability combinations for O 2 /N 2 overcome the typical trade-off between permeability and selectivity, falling above Robeson's 2008 upper-bound limit. Thus, the aim of this work is to report the gas separation performances of six POXINARs synthesized by polymerization of isatines (1a or 1b) with various aromatic hydrocarbons (H− Ar−H) to produce polymers 2aA−D, 2bC, 2bE and 2bF according to the reaction scheme shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%